Experimental study on corrosion of 3D-printed bolts based on metal powder in simulated mine water - Wei YUN; Wei TIAN; Wenkui WANG; Wenhao HE; Lu LI (工程科学学报)
Coal has long been central to China’s energy strategy, with bolt support playing a crucial role in mining operations. As mining depths increase, more challenging conditions emerge, including corrosive underground environments marked by water, high temperatures, humidity, and sulfur-containing media. These factors heighten the demand for durable bolt support systems. Groundwater erosion and mining activities can lead to bolt corrosion and even breakage, making it necessary to develop and study new types of corrosion-resistant bolts. Indoor similarity tests are often used to simulate real bolts, but selecting materials that do not accurately match the mechanical properties and structure of actual bolts can lead to inconsistent results. 3D printing technology enables rapid prototyping and mass production of complex structures with high consistency. The technology offers a high degree of creative freedom, precision, quality, and the ability to create a new type of corrosion-resistant anchors. Investigating the corrosion resistance of bolts made from different materials using 3D printing is crucial for advancing its application in mining. This study utilized electrochemical acceleration methods to assess the corrosion rates, phase compositions, morphological structures, and tensile mechanical properties of 3D-printed bolts made from three different metal powders—stainless steel (SS), die steel (DS), and aluminum alloy (AL)—in a simulated mine water environment, as well as traditional bolts (TBs). The results indicate that, before corrosion, the tensile strength and ductility of 3D-printed SS bolts are closest to those of TBs. The 3D-printed DS bolts have higher corrosion rates and mass-specific corrosion rates at all stages compared to other bolts, while 3D-printed SS bolts exhibit the lowest rates. Both 3D-printed and TB bolts experience varying degrees of corrosion on their surfaces. The surface of 3D-printed SS bolts exhibits only local corrosion, whereas the original surface morphology of 3D-printed DS, AL, and TBs is substantially corroded, resulting in more severe corrosion. The corrosion products of TBs, 3D-printed SS, and 3D-printed DS bolts are similar, mainly composed of Fe2O3, Fe3O4, and FeOOH phases. By contrast, the corrosion products of 3DAL bolts consist solely of Al2O3 and Al(OH)3. After corrosion, the tensile strength and elongation at break of both 3D-printed and TBs decrease to various extents. Corrosion weakly affects the tensile strength and elongation of TBs, whereas 3D-printed SS bolts experience the most significant reduction in tensile strength and ductility after corrosion. The research findings offer valuable insights for designing and assessing the long-term stability of 3D-printed bolts in corrosive mining environments.